Condición femenina y alternativas de organización doméstica : las mujeres sin pareja en São Paulo - Oliveira, Maria Coleta Ferreira Albino de (El Colegio de México A.C., 1992)
The aim of this study is to explore some of the circumstances associated with the type of domestic arrangements of single women in Sao Paulo, Brazil. Unmarried, separated or divorced women, as well as widows, face the risk involved in building a domestic world without connubial bonds. Living without a partner is not the only relevant variable. Other important factors are the existence of children, parents, or other relatives, which influence the organization of day-to-day life.This study focuses upon two central elements. First, the woman’s age, indicating the stage of her life. Second, marital-status differentiating women with previous experience in independent living, which possibly influences her household arrangements. The central question is to determine in what measure these two circumstances affect the way in which single women structure independent household arrangements. A woman's independence is also related to her capacity to build, on her own or with other people, an autonomous day-to-day life, to establish a domestic nucleus that is not based on traditional definitions of gender. In Sao Paulo and in Brazil in general, domestic arrangements organized around a conjugal nucleus predominate. Nevertheless, the recent appearance and increase of other types of arrangements reveal that the conjugal model is not a universally followed pattern. This suggests that there is a strong presence in our milieu of forces directed towards changes in man-woman relationships which are capable of altering expectations and creating new life styles.